Systematic calculations of α-decay half-lives with an improved empirical formula. (9th April 2015) - Wang, Z Y; Niu, Z M; Liu, Q; Guo, J Y
Abstract: Based on the recent data in NUBASE2012, an improved empirical formula for evaluating α -decay half-lives is presented, in which the hindrance effect resulting from the change of the ground state spins and parities of parent and daughter nuclei is included, together with a new correction factor for nuclei near the shell closures. The calculated α -decay half-lives are found to be in better agreement with the experimental data, and the corresponding root-mean-square (rms) deviation is reduced to 0.433 when experimental Q -values are employed. Furthermore, the Q -values derived from different nuclear mass models are used to predict α -decay half-lives with this improved formula. It is found that the calculated half-lives are very sensitive to the Q -values. Remarkably, when mass predictions are improved with the radial basis function (RBF), the resulting rms deviations can be significantly reduced. With the mass prediction from the latest version of Weizsäcker–Skyrme (WS4) model, the rms deviation of α -decay half-lives with respect to the known data falls to 0.697.